THE STATISTICS OF AWARDED DOCTORAL DEGREES: CHANGES AFTER THE REFORM OF THE HIGHER ATTESTATION COMMISSION - S. S. Donetskaya (Moscow Polytechnic University, 2017)
The reform of the Russian scientific training system started in 2013. It was planned to decrease the number of dissertation councils and theses on the humanities, social and economic fields. Four years have passed. Have the number and the structure of awarded doctoral degrees change for this time: by the federal regions and cities of Russia, by the scientific fields and by the types of organizations? The author has tried to give answers to this question. The data for this analysis was taken from abstracts of doctoral theses awarded in 2010 and 2015, which was posted on the website of the Higher Attestation Commission (HAC).